THE SOUNDS PRODUCED BY THE FRICTION OF NORMAL SEROSAE - ORTIZ, TADEO (HOSPITAL GENERAL, CD. MEXICO, DF, MEX, 1939)
The acoustic phenomena produced by friction of organs covered by normal and abnormal serosae, lubricated by normal and abnormal fluids, were studied in rabbits, cats, and dogs. Direct friction of structures covered by normal endothelium, lubricated by nor
AM HEART J
Keywords: SOUNDS, FRICTION, SEROSAE; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA